A Survey on the Adaption of CMS in Pakistani Universities - Hafeez, A.; Javed, S.; Murtaza, A. B.; Aziz, A.; Hassan, S. M.; Hussain, I. (Engineering, Technology & Applied Science Research, 2019)
The use of Campus Management Systems (CMSs) has increased dramatically in Pakistani universities, a huge amount of money has been invested in its development and deployment. The CMS provides an integrated platform for managing academic activities, controlling process flows and provide online access to related information. It improves the efficiency and effectiveness of the universities and eventually improves the quality of teaching. However, it is very important to consider the attitudes and perceptions of faculty members and students towards the adoption of CMS because they may affect the acceptance of this technology. The aim of this study is to investigate and highlight the user satisfaction level about the CMS quality according to ISO/IEC 9126 standard. This work uses cross-sectional design as a primary research method, and data from 105 students and faculty members were collected from a Pakistani public sector university using a questionnaire survey. The response of the respondents illustrates that the system functionality is good, reliable, usable, and efficient. However, some improvements are necessary in some areas such as understandability, learnability, operability, and attractiveness.